Madam Spry and the blue diamond - "Cowley, Joy" (Hawthorn; Mimosa McGraw-Hill, 2007)
Violet Spry, the very sly spy and her faithful hound Hugo, investigate the mystery of the movie star's missing blue diamond. But who's putting on an act? Who's telling the truth?
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Detective and mystery fiction